Fluorine-containing resin dispersion containing a cyclic structure and method for producing the same

CN117700598BActive Publication Date: 2026-10-20SHANDONG DONGYUE WEILAI HYDROGEN ENERGY MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311634040.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-18
Publication Date
2026-10-20
Estimated Expiration
2042-10-18

AI Technical Summary

Technical Problem

[0004]现有用于氢燃料电池离子交换膜的树脂主要是美国Dupont公司的Nafion系列树脂,由长链全氟磺酰乙烯基醚单体与四氟乙烯共聚合得到,其中醚单体的结构为CF2=CFOCF2CF(CF3)OCF2CF2SO2F,该树脂具有化学稳定性好、质子电导率高的特点,但此类树脂的在某些性能方面仍然存在不足,如高温条件下电阻率高,质子导电率低等问题

Benefits of technology

[0066]1.本发明所述的含环状结构的含氟树脂,由聚氟烯烃单元、含环状结构的聚合物单元及含膦酸侧链结构的全氟乙基醚聚合物单元组成的,可通过单体加入量及反应条件等的可调节含环状结构单元及离子交换基团(磺酸和磷酸基团)的含量和比例,在较大范围内调节树脂的交换容量,交换容量为0.5~2.5mmo1/g。且在两种侧链基团的共同作用下,使得含氟树脂不仅高温(大于100℃)条件下具有高的质子传导性和透气性,能够提高高温下的燃料电池效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117700598B_ABST
    Figure CN117700598B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of fluorine-containing resin dispersion and its preparation method, the dispersion includes fluorine-containing resin containing cyclic structure, water and organic solvent, the mass content of the fluorine-containing resin containing cyclic structure in resin dispersion is 1-50%, the mass content of water is 10-90%, the mass content of organic solvent is 5-80%.The fluorine-containing resin is composed of polyfluoroolefin unit, polymer unit containing cyclic structure and perfluoroethyl ether polymer unit containing phosphonic acid side chain structure.The fluorine-containing resin described in the application has good flexibility, excellent mechanical properties, high ion exchange capacity, good gas permeability, low membrane resistance, and can be used for the catalytic layer coating material of fuel cell membrane.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of application No. 202211272339.8 (filed on 2022-10-18, entitled "Fluoropolymer with Ring Structure and Preparation Method Thereof"). Technical Field

[0002] This invention belongs to the field of fluorinated polymer materials, and relates to fluorinated resin dispersions with cyclic structures and their preparation methods. Background Technology

[0003] Fuel cells are a highly efficient, safe, and environmentally friendly energy technology that uses methanol, ethanol, hydrogen, or other fuels to convert chemical energy into electrical energy through an electrochemical reaction. The polymer electrolyte membrane is a core component of the fuel cell, and its performance is crucial for its operation. Perfluorosulfonic acid ion exchange resins have been applied in the chlor-alkali industry and proton exchange membrane fuel cells, demonstrating excellent performance and attracting widespread attention from researchers worldwide. During hydrogen fuel cell operation, hydrogen gas passes through the proton exchange membrane under the action of the anode catalyst and finally reaches the cathode, achieving proton conductivity. Improving the gas permeability of the membrane catalyst layer can significantly enhance the fuel cell's efficiency.

[0004] The resins currently used for ion exchange membranes in hydrogen fuel cells are mainly the Nafion series resins from DuPont, Inc., which are obtained by copolymerizing long-chain perfluorosulfonyl vinyl ether monomers with tetrafluoroethylene. The structure of the ether monomer is CF2=CFOCF2CF(CF3)OCF2CF2SO2F. This resin has good chemical stability and high proton conductivity. However, it still has shortcomings in some properties, such as high resistivity and low proton conductivity at high temperatures. Solvay and Dow have obtained short-side-chain perfluorosulfonic acid resins by copolymerizing short-chain perfluorosulfonyl vinyl ether monomers with tetrafluoroethylene. These resins have higher IEC values, higher mechanical strength, and higher glass transition temperatures than the Nafion series resins. However, their resistivity at high temperatures is still relatively high, and the proton conductivity of the fuel cell membranes prepared from them is still not high enough under high-temperature conditions.

[0005] Chinese patent CN101777657A discloses a doped and cross-linked reinforced resin for perfluorinated proton exchange membranes, which exhibits high proton conductivity and good mechanical properties. CN101237054A discloses a functional fluororesin with good proton conductivity and mechanical properties. However, the resins disclosed in the above patents and literature have high resistivity, and the perfluorinated proton exchange membranes prepared from them have limited effect on improving proton conductivity at high temperatures. Furthermore, when used as a catalyst coating material, their poor permeability makes it difficult to meet the requirements of fuel cells under higher temperature conditions. Summary of the Invention

[0006] To address the technical problems of low proton conductivity and low oxygen permeability of the catalyst layer in fuel cells under high-temperature conditions, this invention provides a fluorinated resin with a cyclic structure and its preparation method.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] A fluorinated resin containing a cyclic structure, comprising polyfluoroolefin units, cyclic polymer units, and perfluoroethyl ether polymer units containing phosphonic acid side chains, having repeating units as shown in formula (I):

[0009]

[0010] In the formula, a = an integer from 2 to 15, b = an integer from 2 to 15, a' = an integer from 1 to 4, and b' = an integer from 1 to 3; x / (x+y) = 0.2 - 0.98, y / (x+y) = 0.02 - 0.8, k = an integer from 0 to 3, and f = an integer from 1 to 4; R is —(OCF2). i (CF2) j X, where X is either Cl or F; i and j are integers from 0 to 3 respectively;

[0011] R1 is R f for

[0012]

[0013] Where m1 and n1 are independent integers from 0 to 4, and m2 and n2 are independent integers from 0 to 4.

[0014] Further preferred, R1 is Rf is

[0015] Where m3 is an integer from 0 to 2, m4 is an integer from 1 to 3, m5 is an integer from 1 to 3, and m6 is an integer from 1 to 3.

[0016] The obtained fluorinated resin has a number-average molecular weight of 100,000-800,000 and a molecular weight distribution (weight-average molecular weight to number-average molecular weight) of 1.0-3.0. The fluorinated resin has a number-average molecular weight of 150,000-400,000 and a molecular weight distribution of 1.0-2.0. More preferably, it has a number of 300,000-400,000.

[0017] The ion exchange capacity of the perfluorinated resin containing cyclic structural units is 0.5–2.8 mmol / g, preferably 0.8–2.5 mmol / g; more preferably 1.05–2.2 mmol / g.

[0018] Preferably, the molar percentage of each polymer unit in the fluorinated resin is as follows: 30-90% for polyfluoroolefin units, 1-65% for cyclic sulfonic acid perfluoropolymer units, and 1-65% for phosphonic acid perfluoropolymer units. More preferably, the molar percentage of polyfluoroolefin units is 40-70%, the molar percentage of cyclic sulfonic acid perfluoropolymer units is 5-30%, and the molar percentage of phosphonic acid perfluoropolymer units is 3-35%. Even more preferably, the molar percentage of cyclic sulfonic acid perfluoropolymer units is 10-20%, and the molar percentage of phosphonic acid perfluoropolymer units is 15-30%.

[0019] Within a certain ratio range, the resulting resin containing phosphonic acid perfluoropolymer units and cyclic sulfonic acid perfluoropolymer units can ensure high proton conductivity and good oxygen permeability of the catalyst layer under high-temperature conditions. The cyclic sulfonyl fluoroolefin ether monomer introduced in this invention has higher exchange capacity and proton conductivity, as well as better thermal stability. As a catalyst layer for fuel cell membrane electrodes, it can increase the operating temperature of the fuel cell and improve the efficiency of the fuel cell at high temperatures.

[0020] The present invention also provides a fluoropolymer containing a cyclic structure, wherein the fluoropolymer undergoes a transformation reaction to obtain the above-mentioned fluoropolymer containing a cyclic structure, and the repeating unit of the fluoropolymer is shown in formula (II):

[0021]

[0022] Where p is an integer from 1 to 3. In equation (II), the values ​​and structure of a, a', b, b', x, y, k, f, R1, and R are the same as in equation (I), and R... f1 The structure is the same as that of the corresponding monomer.

[0023] This invention provides a method for preparing the fluoropolymer shown in formula (II), comprising the following steps:

[0024] Fluoroolefin monomers, cyclic sulfonyl fluoroolefin ether monomers, and phosphonate-containing olefin ether monomers, under the action of an initiator, undergo a copolymerization reaction to obtain a cyclic fluoropolymer of formula (II).

[0025] The sulfonyl fluoroene ether monomer containing a cyclic structure has the following structural formula:

[0026]

[0027] Where R2 is CF2 = C<, or —CF = CF—; R f1 The structure is or Where m1 and n1 are independent integers from 0 to 4, and m2 and n2 are independent integers from 0 to 4.

[0028] Preferred, R f1 for or Where m3 is an integer from 0 to 2, m4 is an integer from 1 to 3, m5 is an integer from 1 to 3, and m6 is an integer from 1 to 3.

[0029] Preferably, the sulfonyl fluoroene ether monomer containing a cyclic structure has the following structural formula:

[0030]

[0031] The preferred structural formula of the phosphonate-containing alkenyl ether monomer of this invention is:

[0032]

[0033] Where k is an integer from 0 to 3, f is an integer from 1 to 4, and p is an integer from 1 to 3. Preferably, k = 1 and f = 2.

[0034] Preferably, the copolymerization reaction time is 2 to 12 hours, the reaction temperature is 20 to 120°C, the preferred temperature is 30 to 90°C, and more preferably 70 to 90°C; the reaction pressure is 0.01 to 10 MPa, preferably 1 to 5 MPa, and more preferably 2.5 to 3.5 MPa.

[0035] Preferably, the initiator used in the copolymerization reaction is selected from one or more of peroxides, perfluoroalkyl peroxides, N2F2, azo compounds, persulfates, and redox systems. More preferably, the perfluoroalkyl peroxide is one or more of CF3CF2CF2CO-OO-COCF2CF2CF3, or CF3CF2CF2OCFCF3CO-OO-COCFCF3OCF2CF2CF3; and the persulfate is one or more selected from ammonium persulfate and potassium persulfate.

[0036] Preferably, the molar ratio of the fluoroolefin monomer, the sulfonyl fluoroolefin monomer containing a cyclic structure, the phosphonate-containing olefin ether monomer, and the initiator is (5-15):(1-10):(5-20):(0.0001-0.01); more preferably (5-15):(1-10):(5-20):(0.001-0.005).

[0037] Preferably, the copolymerization reaction is a dispersion polymerization reaction carried out in an aqueous phase, and the dispersion stabilizer used in the dispersion polymerization is selected from one or any combination of cationic stabilizers, anionic stabilizers, nonionic stabilizers, reactive stabilizers, or nano-inorganic stabilizers. For example, anionic dispersion stabilizers include sodium fatty acid, sodium dodecyl sulfate, sodium alkyl sulfonate, and sodium alkyl aryl sulfonate; nonionic stabilizers include one or more of nonylphenol polyoxyethylene ether, polyoxyethylene fatty acid, and polyoxyethylene fatty acid ether; reactive stabilizers include potassium perfluorovinyl ether sulfonate, ammonium perfluorovinyl ether sulfonate, and ammonium perfluorovinyl ether phosphonate; and nano-inorganic stabilizers include nano-titanium dioxide and silicon dioxide.

[0038] Based on the total weight of the aqueous phase, the overall mass percentage concentration of the dispersant stabilizer used in the dispersion polymerization reaction in water is 0.5–8%, the mass percentage concentration of the cyclic sulfonyl fluoroolefin monomer in water is 0.5–30%, and the mass percentage concentration of the phosphonate-containing olefin monomer in water is 0.5–25%. Preferably, these concentrations are 2–3%, 4–15%, and 4–10%, respectively.

[0039] Specifically, the steps for preparing polymer (II) by dispersion polymerization in an aqueous phase are as follows:

[0040] 1) Add deionized water, dispersant and stabilizer to the reactor, start the stirring device, evacuate and replace with high-purity nitrogen three times, and evacuate again after the oxygen content is qualified; add sulfonyl fluoroolefin monomer with cyclic structure and phosphonate olefin monomer to the reactor, heat to the reaction temperature and add gaseous fluoroolefin monomer to the reaction pressure, then add initiator to start polymerization.

[0041] 2) During the reaction, fluoroolefin monomers are continuously introduced to maintain a certain reaction pressure. Initiator is added at regular intervals. After a certain reaction time, the addition of initiator is stopped. After the reaction continues for 20 to 60 minutes, the addition of tetrafluoroethylene monomer is stopped.

[0042] 3) The reactor is cooled by a cooling circulation system. At the same time, the unreacted fluoroolefin monomers are recovered, and the dispersion obtained from the reaction is released. The white polymer powder is obtained by high-speed shearing and filtration. After drying, a multi-component precursor resin with sulfonyl fluoride groups and phosphonates is obtained.

[0043] This invention also provides a method for preparing a fluorinated resin of formula (I) from a polymer of formula (II). The polymer of formula (II) and an alkaline solution are reacted under nitrogen protection at 30–90°C for 8–120 h. After the reaction, the mixture is filtered, washed with water, and acid-washed to obtain a fluorinated resin with a cyclic structure. Preferably, the reaction temperature is 40–60°C, and the reaction time is 12–36 h.

[0044] More preferably, the mass ratio of the polymer (II) to the alkaline solution is 1:(3-10); the alkaline solution is any one or more aqueous solutions of sodium hydroxide, potassium hydroxide, sodium bicarbonate, ammonia, and sodium carbonate, and the mass percentage concentration of the alkaline solution is 2-15%, preferably 2-8%.

[0045] The pickling solution is a common strong acid such as nitric acid, sulfuric acid, or hydrochloric acid, or a mixture of strong acids, with a mass percentage concentration of 5-30%, and the pickling time is 24-96 hours. The pickling process involves slowly rinsing the products reacting with the alkaline solution with the acid solution. Preferably, the acid concentration is 5-10%, and the pickling time is preferably 30-60 hours.

[0046] This invention also provides the application of the fluorinated resin (Formula II) in fuel cell membrane electrodes. Specifically, as a binder material for the fuel cell membrane catalyst layer, it facilitates the composite between different resin layers and improves interlayer bonding strength, thereby enhancing the high-temperature proton conductivity and permeability of the fuel cell and improving fuel cell efficiency.

[0047] The purpose of this invention is to provide a perfluorosulfonic acid resin dispersion containing a cyclic structure. The introduction of the side chain units of the cyclic structure can improve the solubility of the fluorinated resin and the gas permeability of the resin film, improve the oxygen permeability and diffusion in the cathode catalyst layer, and still have high proton conductivity under high temperature and low humidity environments.

[0048] The above-mentioned objective of this invention is achieved by the following technical solution:

[0049] The present invention provides a dispersion of a cyclic perfluorinated ion exchange resin, comprising a fluorinated resin (Formula I) containing a cyclic structure, water, and an organic solvent.

[0050] The total content of the fluorinated resin containing the cyclic structure in the resin dispersion is 1%-50%, preferably 3%-40%, and more preferably 5%-30%.

[0051] The total content of pure water in the resin dispersion is 10%-90%, preferably 15%-80%, and more preferably 20%-75%.

[0052] The total content of organic solvent in the resin dispersion is 5%-80%, preferably 10%-70%, and more preferably 15%-60%.

[0053] More preferably, the total content of the fluorinated resin containing the cyclic structure in the resin dispersion is 10-25%, the total content of the organic solvent is 35%-50%, and the balance is water.

[0054] Preferably, the mass ratio of pure water to organic solvent is 0.2 to 3:1, more preferably 0.5 to 1.5:1.

[0055] The organic solvent is one or a mixture of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), n-propanol, isopropanol, and ethanol.

[0056] This invention provides a method for preparing the above-mentioned perfluorosulfonic acid phosphate resin dispersion, the method comprising the following steps:

[0057] (1) Place the perfluorosulfonic acid resin in a mixed solvent of water and organic solvent, stir for 20 min to 5 h, then transfer it to a high pressure vessel and dissolve it under high temperature and high pressure for 1 to 120 hours under inert gas protection to obtain a mixed solution containing perfluorosulfonic acid resin.

[0058] (2) The mixed solution prepared in step (1) is separated by liquid-liquid separation to obtain a highly stable perfluorosulfonic acid resin solution with small particle size and uniform dispersion.

[0059] Preferably, the inert gas is selected from nitrogen, argon or xenon.

[0060] Preferably, the melting temperature is 100℃-320℃, more preferably 120℃-280℃, and even more preferably 180℃-280℃.

[0061] Preferably, the pressure is 1 MPa-30 MPa, more preferably 2 MPa-20 MPa, and even more preferably 3-10 MPa. Even more preferably, it is 3-4.5 MPa.

[0062] Preferably, the liquid-liquid separation method includes distillation and extraction separation. The extraction separation uses carbon tetrachloride extraction to collect the lower layer liquid.

[0063] The resin dispersion described in this invention can be used to prepare fuel cell catalyst layers, and in similar or related fields. This invention also provides the application of the resin dispersion in the preparation of fuel cell catalyst layers and fuel cell membrane electrodes. The micelle size of the dispersion is 100–205 nm.

[0064] The catalyst layer prepared by the perfluorosulfonic acid resin dispersion of the present invention has high proton conductivity, high exchange capacity and high air permeability, which effectively improves the utilization efficiency of the catalyst.

[0065] The specific embodiments of the present invention provide one or more technical solutions, which have at least the following beneficial effects:

[0066] 1. The fluorinated resin with a cyclic structure described in this invention is composed of polyfluoroolefin units, cyclic polymer units, and perfluoroethyl ether polymer units with phosphonic acid side chains. The exchange capacity of the resin can be adjusted within a wide range (0.5–2.5 mmol / g) by regulating the amount of monomers added and reaction conditions, as well as the content and ratio of the cyclic units and ion exchange groups (sulfonic acid and phosphate groups). Furthermore, the combined effect of the two side chain groups results in the fluorinated resin exhibiting high proton conductivity and permeability at high temperatures (above 100°C), thus improving the efficiency of fuel cells at high temperatures.

[0067] 2. The fluorinated resin with a cyclic structure provided by the present invention has a fluorinated main chain structure without hydrocarbons, which endows the resin with excellent chemical stability and high temperature resistance. As a binder material for the catalyst layer of fuel cell membrane electrode, it can also improve the solubility of fluorinated resin and the gas permeability of resin membrane, improve the oxygen permeability and diffusion in cathode catalyst layer, and improve battery efficiency. Attached Figure Description

[0068] Figure 1 This is the infrared spectrum of the fluoropolymer (F-1) of Example 1;

[0069] Figure 2 The infrared spectrum of the fluoropolymer (F-5) in Comparative Example 1 is shown below.

[0070] Figure 3 This is the infrared spectrum of the fluoropolymer (F-6) in Comparative Example 2. Detailed Implementation

[0071] The following embodiments are further illustrations of the present invention, but the invention is not limited thereto. Unless otherwise specified, the reactors used in each embodiment are 5L stainless steel high-pressure reactors, equipped with temperature sensors, pressure sensors, heating circulation systems, cooling circulation systems, stirring motors, internal cooling water pipes, liquid metering pumps, gas feed valves, liquid feed valves, and material discharge valves from the reactor.

[0072] Unless otherwise specified in the following examples, the ion exchange capacity is the result of the conversion of sulfonyl fluoride to sulfonic acid and phosphonate to phosphonite.

[0073] The potassium persulfate, ammonium persulfate, and N2F2 gas used in the synthesis process of this invention are all commercially available. Specifically, the potassium persulfate and ammonium persulfate can be purchased from Sinopharm Group; the N2F2 gas can be purchased from Dongyue Chemical Co., Ltd.

[0074] The tetrafluoroethylene monomer used in the synthesis process of this invention was purchased from Shandong Dongyue Polymer Materials Co., Ltd.; the sulfonyl fluoroene ether monomer containing a cyclic structure was prepared using the methods described in US Patents US20090048424A1 and US7799468; and the phosphonate ether monomer was prepared using the method described in Chinese Patent CN101712639A.

[0075] Example 1

[0076] A method for preparing cyclic fluorinated resins involves adding 3L of deionized water and 75g of fluorinated dispersant CF3CF2(CF2OCF(CF3))2COONH4 to a reactor. The stirring device is activated, and the reactor is evacuated and purged three times with high-purity nitrogen. After testing and confirming that the oxygen content inside the reactor is below 5ppm, a vacuum is applied again. 145g of cyclic sulfonyl fluoride monomer MP-1 and 360g of phosphonate ether monomer F2C=CF-OCF2CF(CF3)O-CF2CF2-PO(C2H5)2 are added to the reactor through a liquid feed valve. Then, tetrafluoroethylene monomer is introduced into the reactor until the pressure reaches 3.1MPa. The temperature is raised to 80℃, and 450mg of potassium persulfate is added using a metering pump to initiate the polymerization reaction. Tetrafluoroethylene monomer was continuously introduced to maintain the reaction pressure at 3.1 MPa. 20 mg of initiator was added to the system every 20 min. After 4 h of reaction, the addition of initiator was stopped. The reaction was allowed to continue for 30 min before the addition of tetrafluoroethylene monomer was stopped.

[0077] The reactor is cooled by a cooling circulation system, and unreacted tetrafluoroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is fed into the post-processing system through a discharge valve. After high-speed shearing, it is filtered and separated to obtain white polymer powder, which is then dried in a 100°C oven to obtain a multi-component precursor resin with sulfonyl fluoride groups and phosphonate esters, i.e., a fluorinated polymer conforming to the structure of formula II, denoted as F-1.

[0078] By determining the elemental content of sulfur and phosphorus in the polymer and combining it with NMR spectroscopy, it was found that the molar percentage of tetrafluoroethylene monomer units in the F-1 polymer structure was 59.7%, the molar percentage of sulfonyl fluoroene ether monomer units containing cyclic structures was 11.5%, and the molar percentage of phosphonate ether monomer units was 28.8%. The ion exchange capacity (total exchange capacity of phosphoric acid and sulfonic acid groups) was 1.88 mmol / g dry resin. GPC determination showed that the number average molecular weight of the resin was 327,000.

[0079] Infrared spectral analysis: 1474 cm⁻¹ -1 The peak at 1260.0 cm⁻¹ represents the vibrational absorption peak of the sulfonyl fluoride group. -1 The strong absorption peak is the stretching vibration absorption peak of the phosphonate group at P=0, 1000 cm⁻¹. -1 Up to 1300cm-1 The absorption peak is caused by the bending vibration of the CF bond, 820 cm⁻¹. -1 and 591cm -1 The characteristic peaks belong to the repeating CF2CF2 units after tetrafluoroethylene copolymerization, 2900-3050 cm⁻¹ -1 The peak at this location represents the hydrocarbon vibration absorption peak of the ethyl group in the phosphate ester.

[0080] Example 2

[0081] The preparation method of fluorinated resin with cyclic structure involves adding 3L of deionized water and 75g of fluorinated dispersant CF3CF2(CF2OCF(CF3))2COONH4 to a reaction vessel, starting the stirring device, evacuating the vessel and purging it with high-purity nitrogen three times. After testing that the oxygen content in the reaction vessel is below 5ppm, the vessel is evacuated again. 190g of sulfonyl fluoroolefin monomer MP-1 with a cyclic structure and 390g of phosphonate olefin monomer F2C=CF-OCF2CF(CF3)O-CF2CF2-PO(C2H5)2 were added to the reactor through the liquid feed valve. Then, tetrafluoroethylene monomer was added to the reactor until the pressure reached 3.2MPa. The temperature was raised to 80℃, and 450mg of potassium persulfate was added using a metering pump to initiate the polymerization reaction. The tetrafluoroethylene monomer was continuously introduced to maintain the reaction pressure at 3.2MPa. 20mg of initiator was added to the system every 20min. After the reaction was carried out for 4h, the addition of initiator was stopped, and the reaction was allowed to continue for 30min before the addition of tetrafluoroethylene monomer was stopped.

[0082] The reactor is cooled by a cooling circulation system, and unreacted tetrafluoroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is fed into the post-processing system through a discharge valve. After high-speed shearing, it is filtered and separated to obtain white polymer powder, which is then dried in a 100°C oven to obtain a multi-component precursor resin with sulfonyl fluoride groups and phosphonate esters, i.e., a fluorinated polymer conforming to the structure of formula II, denoted as F-2.

[0083] By determining the elemental content of sulfur and phosphorus in the polymer and combining it with NMR spectroscopy, it was found that the molar percentage of tetrafluoroethylene monomer units in the F-2 polymer structure was 59.4%, the molar percentage of sulfonyl fluoroolefin ether monomer units containing cyclic structures was 13.7%, and the molar percentage of phosphonate olefin ether monomer units was 26.9%. The total ion exchange capacity was 1.78 mmol / g dry resin. GPC determination showed that the number average molecular weight of the resin was 331,000.

[0084] Example 3

[0085] The preparation method of fluorinated resin with cyclic structure involves adding 3L of deionized water and 75g of fluorinated dispersant CF3CF2(CF2OCF(CF3))2COONH4 to a reaction vessel, starting the stirring device, evacuating the vessel and purging it with high-purity nitrogen three times. After testing that the oxygen content in the reaction vessel is below 5ppm, the vessel is evacuated again. 260g of sulfonyl fluoroolefin monomer MP-1 with a cyclic structure and 235g of phosphonate olefin monomer F2C=CF-OCF2CF(CF3)O-CF2CF2-PO(C2H5)2 were added to the reactor through the liquid feed valve. Then, tetrafluoroethylene monomer was added to the reactor until the pressure reached 3.1MPa. The temperature was raised to 80℃, and 450mg of potassium persulfate was added using a metering pump to initiate the polymerization reaction. The tetrafluoroethylene monomer was continuously introduced to maintain the reaction pressure at 3.3MPa. 20mg of initiator was added to the system every 20min. After 4h of reaction, the addition of initiator was stopped, and the reaction was allowed to continue for 30min before the addition of tetrafluoroethylene monomer was stopped.

[0086] The reactor is cooled by a cooling circulation system, and unreacted tetrafluoroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is fed into the post-processing system through a discharge valve. After high-speed shearing, it is filtered and separated to obtain white polymer powder, which is then dried in a 100°C oven to obtain a multi-component precursor resin with sulfonyl fluoride groups and phosphonate esters, i.e., a fluorinated polymer conforming to the structure of formula II, denoted as F-3.

[0087] By determining the elemental content of sulfur and phosphorus in the polymer and combining it with NMR spectroscopy, it was found that the molar percentage of tetrafluoroethylene monomer units in the polymer structure was 65.2%, the molar percentage of sulfonyl fluoroene ether monomer units containing cyclic structures was 17.1%, and the molar percentage of phosphonate ether monomer units was 17.7%. The total ion exchange capacity was 1.29 mmol / g dry resin. GPC determination showed that the number average molecular weight of the resin was 348,000.

[0088] Example 4

[0089] The preparation method of fluorinated resin with cyclic structure involves adding 3L of deionized water and 75g of fluorinated dispersant CF3CF2(CF2OCF(CF3))2COONH4 to a reaction vessel, starting the stirring device, evacuating the vessel and purging it with high-purity nitrogen three times. After testing that the oxygen content in the reaction vessel is below 5ppm, the vessel is evacuated again. 145g of sulfonyl fluoroolefin monomer MP-2 with a cyclic structure and 395g of phosphonate olefin monomer F2C=CF-OCF2CF(CF3)O-CF2CF2-PO(C2H5)2 were added to the reactor through the liquid feed valve. Then, tetrafluoroethylene monomer was added to the reactor until the pressure reached 3.1MPa. The temperature was raised to 80℃, and 400mg of potassium persulfate was added using a metering pump to initiate the polymerization reaction. The tetrafluoroethylene monomer was continuously introduced to maintain the reaction pressure at 3.1MPa. 20mg of initiator was added to the system every 20min. After the reaction was carried out for 4h, the addition of initiator was stopped, and the reaction was allowed to continue for 30min before the addition of tetrafluoroethylene monomer was stopped.

[0090] The reactor is cooled by a cooling circulation system, and unreacted tetrafluoroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is fed into the post-processing system through a discharge valve. After high-speed shearing, it is filtered and separated to obtain white polymer powder, which is then dried in a 100°C oven to obtain a multi-component precursor resin with sulfonyl fluoride groups and phosphonate esters, i.e., a fluorinated polymer conforming to the structure of formula II, denoted as F-4.

[0091] By determining the elemental content of sulfur and phosphorus in the polymer and combining it with NMR spectroscopy, it was found that the molar percentage of tetrafluoroethylene monomer units in the F-4 polymer structure was 63.4%, the molar percentage of sulfonyl fluoroene ether monomer units containing cyclic structures was 10.5%, and the molar percentage of phosphonate ether monomer units was 26.1%, with an ion exchange capacity of 2.08 mmol / g dry resin. GPC determination showed that the number average molecular weight of the resin was 359,000.

[0092] Comparative Example 1

[0093] Add 3L of deionized water and 75g of fluorinated dispersant CF3CF2(CF2OCF(CF3))2COONH4 to the reactor. Start the stirring device, evacuate the reactor, and replace it with high-purity nitrogen three times. After testing that the oxygen content in the reactor is below 5ppm, evacuate the reactor again. 115g of sulfonyl fluoride linear alkenyl ether monomer CF2=CF-OCF2CF2CF2CF2SO2F and 360g of phosphonate ether monomer F2C=CF-OCF2CF(CF3)O-CF2CF2-PO(C2H5)2 were added to the reactor through the liquid feed valve. Then, tetrafluoroethylene monomer was added to the reactor until the pressure reached 3.1MPa. The temperature was raised to 80℃, and 450mg of potassium persulfate was added using a metering pump to initiate the polymerization reaction. The tetrafluoroethylene monomer was continuously introduced to maintain the reaction pressure at 3.1MPa. 20mg of initiator was added to the system every 25min. After 4h of reaction, the addition of initiator was stopped, and the reaction was allowed to continue for 30min before the addition of tetrafluoroethylene monomer was stopped.

[0094] The reactor is cooled by a cooling circulation system, and unreacted tetrafluoroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is fed into the post-processing system through a discharge valve. After high-speed shearing, it is filtered and separated to obtain white polymer powder, which is then dried in a 100°C oven to obtain a multi-component precursor resin with sulfonyl fluoride groups and phosphonate esters, denoted as F-5.

[0095] By determining the elemental content of sulfur and phosphorus in the polymer and combining it with NMR spectroscopy, it was found that the molar percentage of tetrafluoroethylene monomer units in the polymer structure was 59.1%, the molar percentage of sulfonyl fluoride linear ether monomer units was 14.1%, and the molar percentage of phosphonate ether monomer units was 25.9%. The total ion exchange capacity was 1.86 mmol / g dry resin. GPC determination showed that the number average molecular weight of the resin was 337,000.

[0096] Infrared spectral analysis: 1472 cm⁻¹ -1 The peak at 1265.0 cm⁻¹ represents the vibrational absorption of the sulfonyl fluoride group. -1 The strong absorption peak is the stretching vibration absorption peak of the P=O group of the phosphonate ester group, 1000 cm⁻¹. -1 Up to 1300cm -1 The absorption peak at 770 cm⁻¹ is caused by the bending vibration of the CF bond. -1 and 591cm -1 The characteristic peaks belong to the repeating CF2CF2 units after tetrafluoroethylene copolymerization, 2900-3050 cm⁻¹ -1 The peak at this location corresponds to the hydrocarbon vibration absorption peak of the ethyl group in the phosphate ester. The oxygen permeability coefficient of the resulting resin is 0.63 × 10⁻⁶. -13 cm 3 ·cm. / (cm 2The resistivity (·s·Pa) is significantly higher than that of the resin obtained in this invention at temperatures above 120°C. This indicates that the synergistic promoting effect of the various functional groups in this invention also improves the proton conductivity of the resin under high-temperature conditions.

[0097] Comparative Example 2

[0098] Add 3L of deionized water and 75g of fluorinated dispersant CF3CF2(CF2OCF(CF3))2COONH4 to the reactor. Start the stirring device, evacuate the reactor, and purge with high-purity nitrogen three times. After testing and confirming that the oxygen content in the reactor is below 5ppm, evacuate the reactor again. Add 145g of sulfonyl fluoride monomer with a cyclic structure (same as in Example 1) to the reactor through the liquid feed valve. Charge the reactor with tetrafluoroethylene monomer to a pressure of 3.1MPa, raise the temperature to 80°C, and add 450mg of potassium persulfate using a metering pump to initiate the polymerization reaction. Continuously introduce tetrafluoroethylene monomer to maintain the reaction pressure at 3.1MPa. Add 20mg of initiator to the system every 25min. After reacting for 4h, stop adding the initiator and allow the reaction to continue for 30min before stopping the addition of tetrafluoroethylene monomer.

[0099] The reactor is cooled by a cooling circulation system, and unreacted tetrafluoroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is fed into the post-processing system through a discharge valve. After high-speed shearing, it is filtered and separated to obtain white polymer powder, which is then dried in a 100°C oven to obtain a multi-component precursor resin with sulfonyl fluoride groups and phosphonate esters, denoted as F-6.

[0100] NMR and IR analyses confirmed it to be a multi-component precursor resin. By determining the sulfur and phosphorus content in the polymer and combining this with the NMR spectrum, it was found that the molar percentage of tetrafluoroethylene monomer units in the polymer structure was 88.4%, and the molar percentage of sulfonyl fluoroene ether monomer units containing cyclic structures was 11.6%. The overall ion exchange capacity was 1.11 mmol / g dry resin. GPC analysis determined the number-average molecular weight of the resin to be 317,000.

[0101] Infrared spectral analysis: 1468cm -1 The peak at 1100 cm⁻¹ represents the vibrational absorption peak of the sulfonyl fluoride group. -1 -1300cm -1 The vibrational absorption peak belongs to CF, 525 cm⁻¹ -1 and 636cm -1 The characteristic peaks belong to the CF2CF2 repeating unit after tetrafluoroethylene copolymerization.

[0102] Comparative Example 3

[0103] The polymer (denoted as F-7) and resin (H-7) were prepared according to the method described in Example 1 of Chinese Patent Document CN101768236A. Their oxygen permeability coefficient is 0.15 × 10⁻⁶. -13 cm 3 ·cm. / (cm 2 The resistivity of the resin at temperatures above 100°C is significantly higher than that of the resin obtained in this invention, indicating that the resin of this invention, under different combinations of functional groups, also improves the proton conductivity of the resin under high-temperature conditions, especially above 100°C.

[0104] Methods for preparing fluorinated resins and fluorinated resin films from the polymers of Examples 1-4 and Comparative Examples 1-2:

[0105] First, the fluoropolymers obtained in Examples 1-4 were extruded into granules using a small melt extruder. The extrusion temperatures of the melt extruder were set as follows: screw zone 1 250°C, screw zone 2 255°C, screw zone 3 260°C, extruder die temperature 270°C, and extruder die diameter 3mm. By adjusting the shear rate, the cylindrical transparent material extruded from the melt extrusion was sheared to prepare transparent resin granules with a length of 2-4mm. 15g of the sheared granules were placed in 200g of a 5% sodium hydroxide solution and stirred continuously at 50°C for 12 hours. The resin was then filtered, washed with deionized water until neutral, and then placed in an 8% hydrochloric acid solution and stirred for 48 hours. After filtration and washing with deionized water until neutral, solid resin was obtained, which is the fluoropolymer containing a cyclic structure, and designated as H-1, H-2, H-3, and H-4, respectively. The polymers obtained in Comparative Examples 1-2 were treated in the same way to obtain the corresponding fluoropolymers, designated as H-5 and H-6, respectively.

[0106] Fluoropolymer membrane: The white powder products obtained in Examples 1-4 were hot-pressed and vulcanized in a flat vulcanizing machine with the upper and lower heating plates set at 240°C to obtain a transparent film with a thickness of 0.5-2 mm. The prepared film was then sequentially immersed in a 5% sodium hydroxide solution at 80°C for 24 hours, washed with a 10% nitric acid solution (HNO3) at 30°C, and washed with flowing deionized water. The sulfonyl fluoride (-SO2F) side group in the film was converted to the sulfonic acid ion (-SO3H) form, and the (-PO(OR)2) side group in the phosphonate ester was converted to the phosphorous acid (-PO3H2) form. The membrane material was then wound up, sealed, and stored to obtain a fluoropolymer membrane for subsequent resistivity testing. Membrane products (M-1)-(M-4), (D-1)-(D-3) were prepared from the melt-extruded fluorine-containing ion exchange resins prepared in Examples 1-4 and Comparative Examples 1-3.

[0107] Performance testing:

[0108] The mechanical properties of the fluorinated resin with cyclic structure prepared above were tested according to GB / T1040-92. The test temperature was 25-30℃, the test humidity was less than 50%, the test was conducted on type II specimens, the length of the test specimen was 115mm, the distance between the fixtures was 80mm, and the tensile speed was 50mm / min.

[0109] The ion exchange capacity and melt index of fluorinated resins were tested according to GB / T 30296-2013 and GB / T3682-2000, respectively.

[0110] Method for testing the resistivity of fluoropolymer resin: The resistance R of the sample was measured using the two-electrode method. The instrument used was an Autolab PGSTA302 electrochemical workstation with a frequency range of 106 Hz-10 Hz. The resistivity was calculated using the formula: ρ = RS / L, where: L is the thickness of the film (cm), R is the resistance of the film (Ω), ρ is the resistivity of the sample (Ω·cm), and S is the area of ​​the sample being tested (cm²). 2 The resistivity of the fluorinated resin was tested at 100℃, 120℃, and 150℃ respectively.

[0111] Test method for gas permeability: The oxygen permeability was tested according to GB / T 1038-2000. The test results are shown in Table 2.

[0112] Table 1

[0113]

[0114] Table 2

[0115]

[0116]

[0117] The oxygen permeability coefficient of the resin obtained by this invention is 3.16–3.7 × 10⁻⁶. -13 cm 3 ·cm. / (cm 2 The resistivity at 105℃ is 48.5–49.5 Ω·cm (·s·Pa), at 130℃ it is 27–28 Ω·cm, and at 155℃ it is 14–15 Ω·cm. The melt index is 8–9 g / 10 min. The resin obtained by combining cyclic polymer units and phosphate monomer units exhibits excellent permeability and low high-temperature resistance. In contrast, resins obtained by polymerizing tetrafluoroethylene alone with either cyclic or phosphate monomers have low permeability. The permeability significantly increases after combining the two groups.

[0118] Example 5:

[0119] Prepare a 2 kg mixture of water and DMF, with water comprising 50% by mass. Add 360 g of the resin prepared in Example 1 to the mixture, stir for 30 min, then transfer to an autoclave. Under nitrogen protection, mechanically stir, maintain the temperature at 180°C and 3.1 MPa for 8 hours. After cooling to room temperature, remove the mixture and separate it by carbon tetrachloride extraction at room temperature and pressure. The lower layer is then collected. This yields a perfluorosulfonic acid resin dispersion. Visually, no insoluble matter is observed in the dispersion.

[0120] The resulting dispersion contained 18.43% perfluorinated ion exchange resin, 41.5% water, and 40.07% DMF.

[0121] Catalyst ink was prepared by mixing 3g of carbon-supported platinum catalyst powder (purchased from Shanghai Chuxi Industrial Co., Ltd., platinum content 40%) with 61g of water, 15g of n-propanol, and 7g of the resin solution obtained above. The catalyst ink was thoroughly mixed by ball milling and then molded onto polytetrafluoroethylene to obtain a catalyst layer. The catalyst layer was then transferred to the surface of a composite proton exchange membrane (commercially available DMR100 membrane) by applying pressure and heating, resulting in a platinum loading of 0.3 mg / cm³. 2 The membrane electrode.

[0122] Example 6:

[0123] Prepare a 2 kg mixture of water, DMSO, and isopropanol, with water comprising 40% by mass. Add 410 g of the resin prepared in Example 2 to the mixture. After stirring for 1 hour, transfer the mixture to an autoclave, purge with nitrogen, and mechanically stir. Maintain the temperature at 220°C and the pressure at 4.2 MPa for 5 hours. After cooling to room temperature, remove the mixture and extract it using carbon tetrachloride at room temperature and pressure. The lower layer is then collected to obtain the perfluorosulfonic acid resin dispersion. Visually, no insoluble matter is observed in the dispersion.

[0124] The resulting dispersion contained 23.09% perfluorinated ion exchange resin, 32.74% water, 39.37% DMF, and 4.8% isopropanol.

[0125] The membrane electrode was prepared according to the method in Example 5, and a platinum loading of 0.3 mg / cm² was obtained. 2 The membrane electrode contains 5.6g of resin dispersion.

[0126] Example 7:

[0127] Prepare a 2 kg mixture of water, ethanol, and NMP, with water comprising 60% by mass. Add 250 g of the resin prepared in Example 3 to the mixture and stir for 1.5 hours. Transfer the mixture to an autoclave and maintain the stirring under nitrogen protection. Maintain the temperature at 280°C and the pressure at 4.2 MPa for 7 hours. After cooling to room temperature, remove the mixture and separate it by carbon tetrachloride extraction at room temperature and pressure. The lower layer is then collected to obtain the perfluorosulfonic acid resin dispersion. Visually, no insoluble matter is observed in the dispersion.

[0128] The resulting dispersion contained 13.22% perfluorinated ion exchange resin, 51.37% water, 28.72% NMP, and 6.69% ethanol.

[0129] The membrane electrode was prepared according to the method in Example 5, and a platinum loading of 0.3 mg / cm² was obtained. 2 The membrane electrode contains 9.7g of resin dispersion.

[0130] Example 8:

[0131] Prepare a 2 kg mixture of water, ethanol, and DMF, with water comprising 50% by mass. Add 320 g of the resin prepared in Example 4 to the mixture and stir for 45 min, then transfer to an autoclave. Under nitrogen protection, mechanical stirring is performed at 250°C and 3.9 MPa for 7 hours. After cooling to room temperature, the mixture is removed and extracted with carbon tetrachloride at room temperature and pressure. The lower layer is then collected to obtain the perfluorosulfonic acid resin dispersion. Visually, no insoluble matter is observed in the dispersion.

[0132] The resulting dispersion contained 15.78% perfluorinated ion exchange resin, 37.56% water, 16.73% DMF, and 29.93% ethanol.

[0133] The membrane electrode was prepared according to the method in Example 5, and a platinum loading of 0.3 mg / cm² was obtained. 2 The membrane electrode contains 8.1 g of resin dispersion.

[0134] Comparative Example 1

[0135] Prepare a 2 kg mixed solution of water, n-propanol, and DMF, wherein the water mass fraction is 50%, and add a perfluorosulfonic acid resin with an exchange capacity of 1.1 mmol / g (resin structure is...). 380g of a polymer (molecular weight 320,000) was mixed and stirred for 1 hour, then transferred to an autoclave. Nitrogen gas was used for stirring, and the temperature was controlled at 200℃ and the pressure at 3.4MPa for 7 hours. After cooling to room temperature, the mixed solution was removed and separated by carbon tetrachloride extraction at room temperature and pressure. The lower layer solution was then collected to obtain the perfluorosulfonic acid resin dispersion. Visual inspection revealed no insoluble matter in the dispersion.

[0136] The resulting dispersion contained 20.98% perfluorinated ion exchange resin, 41.93% water, 20.34% DMF, and 16.75% n-propanol.

[0137] The membrane electrode was prepared according to the method in Example 5, and a platinum loading of 0.3 mg / cm² was obtained. 2 The membrane electrode contains 6.1 g of resin dispersion.

[0138] Comparative Example 2

[0139] Prepare a 2 kg mixed solution of water, DMAc, and isopropanol, wherein the water mass fraction is 40%, and add a perfluorosulfonic acid resin with an exchange capacity of 1.2 mmol / g (resin structure is...). 110g of a perfluorosulfonic acid resin (molecular weight 330,000) was mixed and stirred for 50 minutes, then transferred to an autoclave. Nitrogen gas was introduced for protection, and mechanical stirring was performed. The temperature was controlled at 180℃ and the pressure at 2.7MPa, and the mixture was held at this temperature for 6 hours. After cooling to room temperature, the mixed solution was removed and separated by carbon tetrachloride extraction at room temperature and pressure. The lower layer was then collected to obtain the perfluorosulfonic acid resin dispersion. Visual inspection revealed no insoluble matter in the dispersion.

[0140] The resulting dispersion contained 5.9% perfluorinated ion exchange resin, 42.48% water, 34.46% DMAc, and 17.16% isopropanol.

[0141] The membrane electrode was prepared according to the method in Example 5, and a platinum loading of 0.3 mg / cm² was obtained. 2 The membrane electrode contains 21.8 g of resin dispersion.

[0142] The solid content of the resin dispersion was measured using a halogen analyzer, and the viscosity was measured using a Shanghai Jinghai NDJ-8S viscometer. The micelle size was measured using a Brookhaven particle size analyzer. Smaller ionomer micelle sizes in the resin dispersion result in more uniform catalyst dispersion and higher proton conductivity of the catalyst layer.

[0143] Fabrication of a single fuel cell: The same gas diffusion layer, bipolar plate, and support plate (Ballard GDS 3260 gas diffusion layer, Qunyi serpentine flow channel bipolar plate) are stacked on both poles of the membrane electrode obtained in the examples or comparative examples to form a fuel cell.

[0144] Catalytic layer local current density test: The above-mentioned fuel cell single cell was set in the Qunyi 850Es fuel cell evaluation device, and a local transmission impedance test experiment was carried out.

[0145] The test conditions are as follows: (1) The battery temperature is 90℃, humidified at 100%RH, and the pressure is 0KPa, 50KPa, 100KPa, 150KPa, 200KPa. After the voltage stabilizes at 0.15V for 20 minutes, the final stable current density value is taken; (2) The battery temperature is 90℃, the pressure is 0Kpa, and the current density value is taken after stabilizing at 0.15V for 20 minutes under the humidity conditions of 10%RH, 30%RH, 50%RH, 70%RH, and 100%RH respectively.

[0146] The impedance range of a fuel cell membrane electrode is classified into three categories: molecular diffusion impedance, Knudsen diffusion impedance, and local ionomer diffusion impedance. Molecular diffusion impedance is caused by the gas diffusion layer, Knudsen diffusion impedance is caused by the catalyst layer, and local ionomer diffusion impedance is caused by the ionomers in the catalyst layer. The purpose of this test scheme (1) is to extract the diffusion impedance of the catalyst layer, and the purpose of test scheme (2) is to separate the Knudsen diffusion impedance and the local ionomer diffusion impedance.

[0147] The sample test results are summarized in Table 3.

[0148] Table 3. Performance data of resin solutions and catalyst layers in Examples 5-8 and Comparative Examples 1 and 2.

[0149]

Claims

1. A fluorinated resin dispersion containing a cyclic structure, characterized in that, The mixture comprises a fluorinated resin containing a cyclic structure, water, and an organic solvent, wherein the fluorinated resin containing the cyclic structure has a mass content of 1-50% in the resin dispersion, the water has a mass content of 10-90%, and the organic solvent has a mass content of 5-80%. The fluorinated resin containing the ring structure has the structure shown in formula (I): Formula (I) In the formula, a = an integer from 2 to 15, b = an integer from 2 to 15, a' is an integer from 1 to 4, and b' is an integer from 1 to 3; x / (x+y) = 0.2 - 0.98, y / (x+y) = 0.02 - 0.8, k is an integer from 0 to 3, and f is an integer from 1 to 4; R is -(OCF2). i (CF2) j X, where X is either Cl or F; i and j are integers from 0 to 3 respectively; R1 is ;R f for ,or Where m1 and n1 are independent integers from 0 to 4, and m2 and n2 are independent integers from 0 to 4; the bonds marked "*" are bonds connected to O atoms.

2. The fluorinated resin dispersion containing a cyclic structure according to claim 1, characterized in that, R f for or Where m3 is an integer from 0 to 2, m4 is an integer from 1 to 3, m5 is an integer from 1 to 3, and m6 is an integer from 1 to 3.

3. The fluorinated resin dispersion containing a cyclic structure according to claim 1, characterized in that, Fluoropolymers containing cyclic structures have a number-average molecular weight of 100,000 to 800,000; and an ion exchange capacity of 0.5 to 2.8 mmol / g.

4. The fluorinated resin dispersion containing a cyclic structure according to claim 3, characterized in that, Fluoropolymers containing cyclic structures have a number-average molecular weight of 150,000 to 400,000.

5. The fluorinated resin dispersion containing a cyclic structure according to claim 1, characterized in that, The percentage of molar content of each polymer unit in the fluorinated resin containing a cyclic structure is as follows: 30-90% for polyfluoroolefin units, 1-65% for sulfonic acid perfluoropolymer units containing a cyclic structure, and 1-65% for phosphonic acid perfluoropolymer units.

6. The fluorinated resin dispersion containing a cyclic structure according to claim 5, characterized in that, The molar content of polyfluoroolefin units is 40-70%, the molar content of sulfonic acid perfluoropolymer units with cyclic structures is 5-30%, and the molar content of phosphonic acid perfluoropolymer units is 3-35%.

7. The fluorinated resin dispersion containing a cyclic structure according to claim 1, characterized in that, The fluorinated resin containing a cyclic structure has a mass content of 3-40% in the resin dispersion, a water mass content of 15-80% in the resin dispersion, and an organic solvent mass content of 10-70%.

8. The fluorinated resin dispersion containing a cyclic structure according to claim 7, characterized in that, The fluorinated resin containing a cyclic structure has a mass content of 5-30% in the resin dispersion, a water mass content of 20-75% in the resin dispersion, and an organic solvent mass content of 15-60%.

9. The fluorinated resin dispersion containing a cyclic structure according to claim 8, characterized in that, The fluorinated resin containing a cyclic structure has a mass content of 10-25% in the resin dispersion, the organic solvent has a mass content of 35%-50%, and the balance is water.

10. The fluorinated resin dispersion containing a cyclic structure according to claim 1, characterized in that, The organic solvent is one or a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, n-propanol, isopropanol, and ethanol.

11. A method for preparing the dispersion according to any one of claims 1 to 10, characterized in that, Includes the following steps: (1) Place the fluorinated resin containing the cyclic structure in a mixed solvent of water and organic solvent, stir for 20 min to 5 h, then transfer it to a high pressure vessel and dissolve it under high temperature and high pressure for 1 to 120 hours under inert gas protection to obtain a mixed solution of the fluorinated resin containing the cyclic structure. (2) The mixed solution prepared in step (1) is separated by liquid-liquid separation to obtain a fluorinated resin dispersion with small particle size and uniform dispersion containing a ring structure.

12. The preparation method according to claim 11, characterized in that, The dissolution temperature for step (1) is 100℃-320℃.

13. The preparation method according to claim 12, characterized in that, The dissolution temperature for step (1) is 120℃-280℃.

14. The preparation method according to claim 13, characterized in that, The dissolution temperature for step (1) is 180℃-280℃.

15. The preparation method according to claim 11, characterized in that, Step (1) The pressure is 2MPa-20MPa.

16. The preparation method according to claim 15, characterized in that, Step (1) The pressure is 3~10MPa.

17. The preparation method according to claim 16, characterized in that, Step (1) The pressure is 3~4.5MPa.

18. The preparation method according to claim 11, characterized in that, The liquid-liquid separation method in step (2) is distillation and extraction separation.

Citation Information

Patent Citations

  • An intercrossed enhanced full fluorin proton adulterated exchange film and its making method

    CN101237054A

  • Method for preparing functional fluorine-bearing monomer by vertical-tube type catalytic reaction

    CN101712639A

  • Perfluorinated ion exchange resin as well as preparation method and application thereof

    CN101768236A

  • Fluorine-containing proton exchange membrane for fuel cell prepared by using functional fluororesin

    CN101777657A

  • Fluorosulfonyl group-containing monomer and its polymer, and sulfonic acid group-containing polymer

    US20090048424A1